Identification of Fungi and Yeasts from the Sands of the Pyramids of Giza, in Cairo, Egypt - Echevarría, Lourdes; Iqbal, Muhammad Naeem (PSM Biological Research, 2021)
The pyramids in Egypt have many visitors annually, especially during the summer. Many tourists get sick, probably from being exposed to the wind, which mostly contains sand particles. The samples were collected in July 2019. The objective of this research was to know the diversity and quantity of filamentous fungi and yeasts in the dry sands of the pyramids. To determine if the fungi found are pathogenic for man. One gram of sample was taken in triplicate and spread on each plate with culture medium; RBA, SDA, PDA, and Hardy ChRom. The samples were incubated for 7 to 14 days at 25 ° C. Colonies were counted and then species were isolated in tubes of each medium. Six genera were found: Aspergillus, Penicillium, Rhizopus, Candida, Alternaria, and Hortaea. The Aspergillus and Candida species showed more growth. The average of filamentous fungi and yeasts in the samples ranged from 13 CFU / g to 21 CFU / g. This indicates that the sand according to the results would be of average quality. The species identified were A. niger, A. flavus, R. stolonifer, P. raistrickii, Hortaea werneckii, Alternaria, C. glabrata, and C. tropicalis. Most of the yeasts and filamentous fungi identified are pathogenic to humans. Some of the identified species develop several diseases, so people with weak immune systems will need to protect themselves. It is advisable to cover the mouth, nose, and wear glasses for the eyes so that the spores cannot access the chemical and physical barriers of our body.